Association Between Dietary Inflammatory Index and Sex Hormone Binding Globulin and Sex Hormone in U.S. Adult Females - Nuozhou Liu; Ying Feng; Xinyao Luo; Xue Ma; Fang Ma; Fang Ma (Frontiers Media S.A., 2022)
ContextIt is still unknown whether the dietary inflammatory index (DII) is associated with sex hormones and sex hormone binding globulin (SHBG) in adult women.ObjectiveThis study examined the association between DII and sex hormones and SHBG in U.S. adult women.Design and ParticipantsThis was a cross-sectional study. A total of 2,092 female participants (age ≥ 20) from the 2013-2016 National Health and Nutrition Examination Survey were enrolled. Dietary inflammatory potential was assessed by DII based on 24-h dietary recall. SHBG was assessed using immuno-antibodies and chemo-luminescence, whereas sex hormones were measured by ID-LC-MS/MS.ResultsThe average DII was 0.21 ± 1.68, ranging from −4.54 (most anti-inflammatory) to 4.28 (most pro-inflammatory). After adjusting all covariates, a per-unit DII increase in DII tertile 3 was related to an 8.05 nmol/L SHBG decrease compared to DII tertile 1 (P = 0.0366). Subgroup analysis stratified by perimenopausal period found that this negative association remained strong but only existed in women before (β = −3.71, 95% CI: −7.43, −0.12, P = 0.0423) the perimenopausal period. Interaction terms were added to both subgroup analyses and found no significant heterogeneity among different body mass index (BMI) or perimenopausal groups (P > 0.05). Treshold analyses showed that the association of age with SHBG was an inverted U-shaped curve (inflection point: age = 50 yrs).ConclusionA proinflammatory diet caused decreased SHBG. However, more well-designed studies are still needed to validate and verify the causal relationship between DII and sex hormones and SHBG.